PERISTIWA ENTREPRENEURIAL: TINJAUAN DAN PENGEMBANGAN PEMIKIRAN SHAPERO DALAM CERITA TIGA WIRAUSAHA DI BALI - Roni Tua (Business Administration Department - Universitas Katolik Parahyangan, 2022)
The corpus of academic literature on entrepreneurship is progressing rapidly, which could lead to negligence for classical ideas that may still be pertinent and contextually necessary to be developed. The unanswered topic of what attributes attach to an entrepreneur and give rise to the label